Extraction and purification of green polymers using aqueous two-phase extraction (ATPE) - Leong, Yoong Kit (2018)
Due to the increasing concern towards depleting petroleum resource and pollutions done by conventional plastics, polyhydroxyalkanoates (PHAs) which have diverse structure variability and rapid biodegradation have gained increasing attentions as potential replacement for plastics. However, PHAs have a much higher production cost compared to that of conventional plastics due to expensive carbon source and downstream processing. Aqueous two-phase extraction (ATPE) outshines other PHAs purification techniques by having the advantages of providing a mild environment for bioseparation, being green and non-toxic, and easily scaled-up. Henceforth, this research aimed to study on the purification and recovery of PHAs using thermoseparation-based ATPE.